Strain capacity assessment of API X65 steel using damage mechanics - Gabriel Testa; Nicola Bonora; Domenico Gentile; Andrew Ruggiero; Gianluca Iannitti; Antonio Carlucci; Yazid Madi (Fracture and Structural Integrity)
Strain-based design for offshore pipeline requires a considerable experimental work aimed to determine the material fracture toughness and the effective strain capacity of pipe and welds. Continuum damage mechanics can be used to limit the experimental effort and to perform most of the assessment analysis and evaluation in a simulation environment. In this work, the possibility to predict accurately fracture resistance of X65 steel using a CDM model proposed by the authors, is shown. The procedure for material and damage model parameters identification is presented. Damage model predictive capability was demonstrated predicting ductile crack growth in SENB and SENT fracture specimens.